Triple condensate halo from a single water droplet impacting upon a cold surface - Zhao, Yugang (2019)
Understanding the dynamics of water droplets impacting upon a solid surface is of importance from both fundamental and practical standpoints. While the impact dynamics of a water droplet upon a heated surface has been extensively studied, the impact characteristics of droplets upon a cold surface remain elusive. Here, we report the formation of a triple condensate halo observed during a water droplet impacting at low velocity upon a cold surface. Due to the interplay of droplet impact and vapor mass diffusion during the droplet spreading and cooling processes, two condensation stages occur, engendering this unique condensate halo with three distinctive bands. We further examine experimentally the effects of droplet impact velocity (in terms of Weber number) and substrate temperature on the three bands of condensate halo. We also provide scaling analyses to explain the experimental results. Our experimental investigation and theoretical analysis reported in this study reveal insights into the droplet impact dynamics and the associated condensation heat transfer.